(untitled) (Bangladesh Armed Forces Medical Journal, 2026)
Background: Zonular dehiscence (ZD), referred to as the presence of deficient zonular support for the lenticular capsule, might be the result of several causes and be detected only at the time of cataract surgery. The aim of this study was to evaluate variety of visual outcome of pre-, intra-, and postoperative features of eyes with ZD regardless of the etiology detected during Phacoemulsification. Methods: A single center descriptive case series study was performed at Combined Military Hospital, Dhaka to identify patients’ visual outcome who underwent cataract surgery whose procedure was described intraoperatively as being complicated by various extent of ZD from January 2021 to July 2021. Patient characteristics, intraoperative clinical findings, visual and refractive outcomes and postoperative complication were recorded. Use of CTR routinely in phacoemulsification regardless of whether zonular dehiscence is present to reduce the risk of delayed IOL dislocation or capsular contraction. Results: ZD was identified intraoperative in 30 eyes of patients. Among 30 patients 60% surgery was done in the right eye and 40% were in left eye. Among 67% cases the degree of Zonular dehiscence was <90˚ & for 33% of cases was between 90 -180. Intraoperative complication i.e. posterior capsule rupture occurred in 6.67% patients and dropped nucleus occurred in 3.33% patients. 33.3% eyes had AC IOL, 40% eyes had PCIOL with CTR and 20% eyes had sulcus IOL. Conclusions: ZD is a serious complication of cataract surgery requiring prompt intraoperative diagnosis and proper management. While it tends to worsen cataract surgery outcomes, the implantation of CTRs during the surgical procedure seems to be associated with better postoperative visual and refractive results. Incidence of zonular dialysis is low, surgeons should consider using a Capsular Tension Ring (CTR) upon the extent of ZD during phacoemulsification. This device helps manage the surgical challenges associated with the dialysis, which translates into improved best-corrected visual acuity (BCVA) over the early and intermediate follow-up periods. Bangladesh Armed Forces Med J Vol 58 No (2) December 2025, pp 44-49